Detrainment Dominates CCN Concentrations Around Non‐Precipitating Convective Clouds Over the Amazon. Issue 20 (12th October 2022) - Braga, Ramon C.; Rosenfeld, Daniel; Andreae, Meinrat O.; Pöhlker, Christopher; Pöschl, Ulrich; Voigt, Christiane; Weinzierl, Bernadett; Wendisch, Manfred; Pöhlker, Mira L.; Harrison, Daniel
Abstract: We investigated the relationship between the number concentration of cloud droplets ( N d ) in ice‐free convective clouds and of particles large enough to act as cloud condensation nuclei (CCN) measured at the lateral boundaries of cloud elements. The data were collected during the ACRIDICON‐CHUVA aircraft campaign over the Amazon Basin. The results indicate that the CCN particles at the lateral cloud boundaries are dominated by detrainment from the cloud. The CCN concentrations detrained from non‐precipitating convective clouds are smaller compared to below cloud bases. The detrained CCN particles from precipitating cloud volumes have relatively larger sizes, but lower concentrations. Our findings indicate that CCN particles ingested from below cloud bases are activated into cloud droplets, which evaporate at the lateral boundaries and above cloud base and release the CCN again to ambient cloud‐free air, after some cloud processing. These results support the hypothesis that the CCN around the cloud are cloud‐processed. Plain Language Summary: Interactions of aerosol particles with clouds represent a significant uncertainty in estimates of climate change. Properties of aerosol particles control their ability to act as cloud condensation nuclei (CCN). Accounting for CCN concentrations and sizes available through the evaporation of cloud droplets and raindrops is highly complicated and a crucial challenge for cloud modeling purposes. Based on airborne measurements performed with the German High Altitude and Long Range Aircraft aircraft, we describe a conceptual model for aerosol‐cloud interaction at the lateral boundaries of Amazonian convective clouds. We show that the CCN particles at the lateral boundaries of non‐precipitating convective clouds originate mostly from evaporated cloud droplets. In precipitating clouds, many of the activated CCN merge and scavenged, as indicated by the fewer and larger CCN around the clouds. Key Points: Residual particles from the evaporation of non‐precipitating droplets of convective clouds dominate the cloud condensation nuclei (CCN) concentrations around clouds The CCN enrichment around the clouds diminishes above the height of warm rain initiation Drizzle evaporated from rain clouds leads to the formation of larger CCN particles than droplets evaporated from non‐precipitating clouds